Understanding the importance and context of vilification - Gorman, Sean; Lusher, D.; Reeves, K. (Routledge, 2016)
This paper looks at the context with which the research for the collection came out of. It draws on recent examples in the media and football and connects that up to the examples in the past particularly the incidents in the AFL that involved Nicky Winmar in 1993 and Michael Long in 1995 and the introduction of Rule 35. This paper sets the scene from which the rest of the collection positions itself.